Does National Culture or Ambient Temperature Explain Cross-National Differences in Role Stress? No Sweat! - Peterson, Mark; Smith, Peter B. (Academy of Management Journal, 1997)
Van de Vliert and Van Yperen's (1996) proposal that ambient temperature explains the relationship between national cultural values and typical levels of role stress is reevaluated. The provisional conclusion is that the effect of ambient temperature on role stress is largely mediated by its contribution to the historical evolution of cultural values.